Performance of wild-Serbian Ganoderma lucidum mycelium in treating synthetic sewage loading using batch bioreactor - Mohd Hanafiah, Zarimah; Wan Mohtar, Wan Hanna Melini; Abu Hasan, Hassimi; Jensen, Henriette Stokbro; Klaus, Anita; Wan-Mohtar, Wan Abd Al Qadr Imad (Nature Research, 2019)
The fluctuation of domestic wastewater characteristic inhibits the current conventional microbial-based treatment. The bioremediation fungi has received attention and reported to be an effective alternative to treat industrial wastewater. Similar efficient performance is envisaged for domestic wastewater whereby assessed performance of fungi for varying carbon-to-nitrogen ratios in domestic wastewater is crucial. Thus, the performance of pre-grown wild-Serbian Ganoderma lucidum mycelial pellets (GLMPs) was evaluated on four different synthetic domestic wastewaters under different conditions of initial pH (pH 4, 5, and 7) and chemical oxygen demand (COD) to nitrogen (COD/N) ratio of 3.6:1, 7.1:1, 14.2:1, and 17.8:1 (C3.6N1, C7.1N1, C14.2N1, and C17.8N1). The COD/N ratios with a constant concentration of ammonia–nitrogen (NH3–N) were chosen on the basis of the urban domestic wastewater characteristics sampled at the inlet basin of a sewage treatment plant (STP). The parameters of pH, COD, and NH3–N were measured periodically during the experiment. The wild-Serbian GLMPs efficiently removed the pollutants from the synthetic sewage. The COD/N ratio of C17.8N1 wastewater had the best COD and NH3–N removal, as compared to the lower COD/N ratio, and the shortest treatment time was obtained in an acidic environment at pH 4. The highest percentage for COD and NH3–N removal achieved was 96.0% and 93.2%, respectively. The results proved that the mycelium of GLMP has high potential in treating domestic wastewater, particularly at high organic content as a naturally sustainable bioremediation system. © 2019, The Author(s).